A Study Of 370 Live Births In A Rural Area Of Punjab - Singh Surinder; Singh Tejbir; Goel R.K.D; Singh Jagjeet; Oberoi Satish Kumar; Mittal Sushila (Wolters Kluwer Medknow Publications, 1988)
The study was carried out in12 Anganwadi areas of ferozepur District in Punjab to know about the various aspects of reproduction of the population. A total of 13, 782 population was covered. The sex ratio of the surveyed population was 900.7 females to 1000 males. The crude Birth rate of the area came to be 26.83 per 1000 population. In 94.87% of the births, the delivery occurred at the completion of 36 weeks of Gestation period & majority of the births (91.63%) occurred to the mothers in the age group of 20 to 35 years . 24.86% of the children were born to the mothers with parity of five and above. 46.75% of the births took place between the months of July and October. 96.22% of the deliveries were conducted at home and majority (93.79%) of the mothers utilized the services of indigenous dais( 73.52% of trained dais and 20.27% of untrained dais) for the conduction of delivery.